IMPLEMENTASI PROGRAM PENDIDIKAN INKLUSI DI SEKOLAH DASAR NEGERI KARANGANYAR KOTA YOGYAKARTA - Nurrahmawati, Tania; Putranto, Arif Kuncoro Dwi (PARADIGMA: Jurnal Ilmu Administrasi, 2024)
Implementation of an inclusive education program is the implementation of education that includes efforts to include children with special needs into the general school environment. Inclusive education means that schools must include all children, regardless of physical, intellectual, socio-emotional and language conditions. The aim of inclusive education is to provide the widest possible opportunities for students with special needs to obtain education without discrimination. This research uses a qualitative research approach with descriptive methods. Determining informants in this research used the purposive sampling method. The theory used in this research is Ripley and Franklin's theory in Winarno (2014: 148), namely: the level of compliance with applicable regulations, the smooth implementation of routine functions and the absence of problems, the implementation and desired impacts are directed. The aim of this research is to find out the implementation of the inclusive education program at SDN Karanganyar Yogyakarta and to find out what the obstacles are in implementing the inclusive education program at SDN Karanganyar Yogyakarta.Keyword: Implementation; Education; Inclusion; Inclusive education.